Assessment of thermal environmental conditions and quantification of thermal adaptation in naturally ventilated buildings in composite climate of India. (April 2015) - Dhaka, Shivraj; Mathur, Jyotirmay; Brager, Gail; Honnekeri, Anoop
Abstract: India has diverse climatic conditions and study of adaptation can play important role for defining thermal comfort conditions in naturally ventilated buildings. Therefore, a field study of thermal comfort was carried out in thirty well ventilated residential and office buildings in composite climate region of India. The objective of the study is to evaluate the thermal environmental conditions and quantify thermal adaptation for occupants of these buildings. The study ascertains thermal neutrality and thermal acceptability and compares adaptation with field studies referred by a pool of researchers and scientists. The methodology of the study was through questionnaire administered to building occupants to record sensations and preferences for thermal environment variables. Simultaneously, physical measurements of environment variables were recorded considering class-II protocol of field measurements. During the study, the responses collected were 1811. The comfort temperature of the group was 27.21 °C for all seasons. The effects of seasonal variations on neutral temperature were also determined; respondents felt neutral at 25.6 °C, 27.0 °C and 29.4 °C during winter, moderate and summer seasons, respectively. Acceptable humidity and air velocity were 36% and 0.44 m/s for all seasons. Thermal acceptability for 90% and 80% were higher than the limits defined by comfort standards. Thermal acceptability reflected that study subjects were more adaptive to the thermal environment. The study observed that heat balance model of thermal comfort overestimated and underestimated thermal sensation during warm and cool thermal conditions, respectively. Furthermore, the study determines relationship between room temperature and comfort temperature with outdoor temperature. Highlights: Study revealed that comfort is dependent on outdoor dry bulb temperature. Neutral temperature of the study group was found 27.2 °C for combined seasons. Study observed that neutral temperature varies with seasonal variances. Subject from present study are found more adaptive to the thermal environment. Wider bandwidth of comfort (10 °C) was found for 80 and 90% acceptability limits.